131k views
0 votes
Rationalise the denominator and simplify

User Chembrad
by
5.4k points

2 Answers

4 votes

1

2

3

4

5

6

7

8

9

10

11

12

13

14

15

16

17

18

19

20

User IMDroid
by
5.3k points
4 votes

Explanation:


\bf \underline{Given-} \\


(5 + 2 √(3) )/(7 + 4 √(3) ) \\


\bf \underline{What\: to\: do-} \\

To rationalise the denominator


\bf \underline{Solution-} \\


\textsf{We have,}


(5 + 2 √(3) )/(7 + 4 √(3) ) \\ \\


\textsf{The denominator is 5+2√3. Multiplying the numerator and denominator by 7-4√3,}\\


\textsf{we get,}\\


⟹(5 + 2 √(3) )/(7 + 4 √(3) ) * (7 - 4 √(3) )/(7 - 4 √(3) ) \\ \\


⟹ ((5 + 2 √(3) )(7 - 4 √(3)) )/((7 + 4 √(3) )(7 - 4 √(3)) ) \\ \\


\textsf{⬤ Applying Algebraic Identity</p><p>(a+b)(a-b) = a² - b² to the denominator}\\


\textsf{We get,}\\


⟹ \frac{(5 + 2 √(3) )(7 - 4 √(3)) }{(7 {)}^(2) - (4 √(3) {)}^(2) } \\ \\


⟹ (35 + 14 √(3) - 20 √(3) - 8 √(3 * 3) )/(49 - 48) \\ \\


⟹ (35 + 14 √(3) - 20 √(3) - 24 )/(1) \\ \\


⟹(35 - 24) - 6 √(3) \\ \\


⟹11 - 6 √(3) \: \: \: \tt \red{ Ans}. \\ \\


\bf \underline{Hence \:the \:denominator\: is\: rationalised.}\\

User Kathan Shah
by
5.4k points